Najstarsze statuty wikariuszy katedry gnieźnieńskiej (z roku 1500) - Czyżak, Marta (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The statutes of the vicars of the Gniezno cathedral were composed at the turn of the 15th and 16th century and were in their entirety drawn up by the chapter on 22 June 1499. It was the initiative of Archbishop Fryderyk Jagiellończyk, who was concerned about an unsatisfactory functioning of the College. The initiative was carried out by Klemens from Piotrków, doctor decretalium, a Gniezno canon. On 9 December 1500 the statutem were authorized by Cardinal Fryderyk Jagiellończyk with the chapter and he commanded to have them entered in the matrica capitulari. The statutes survived to our time in a copy made in the 1720s. Description of offenses and the system of punishments in the statues reveal the daily matters and some of the deficiencies of the College: absence from liturgical ministry, drunkenness, quarrels, irregularities of the officium Divinum, careless celebration of choral prayer, conversations and jokes during chants, drowsiness.